The history of the decline and fall of the Roman Empire - Gibbon, Edward, 1737-1794. (London London)
7 cilt (1. c. l, 522 sayfa ; 2. c. xiv, 560 sayfa ; 3. c. xiv, 582 sayfa ; 4. c. xiv, 554 sayfa ; 5. c. xii, 535 sayfa ; 6. c. xiv, 573 sayfa ; 7. c. xviii, 594 sayfa)